2015
DOI: 10.2494/photopolymer.28.181
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Phosphoric Acid-doped Blend Membrane Composed of Sulfonated Poly(arylene ether sulfone) and Polybenzimidazole for Fuel Cell Application

Abstract: A phosphoric acid (PA)-doped blend membrane composed of sulfonated poly(arylene ether sulfone) (SPAES) and polybenzimidazole (PBI) was developed for fuel cell application. Blending of SPAES and PBI improved its dimensional stability and gas barrier properties due to the acid-base interaction. Although the proton conductivity of the blend membrane was lower than that of the pristine SPAES membrane, the PA-doping redeemed its disadvantage to show enough high proton conductivity comparable to the conductivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…25 Liu et al also revealed a new proton transport channel in PA-doped composite membranes composed of poly(arylene ether sulfone) (SPAES) and PBI. 26 Herein, we blended our previously reported sulfonated poly (fluorenyl ether ketone) (SPFEK) with poly [2,2″-(p-oxydiphenylene)−5,5″-benzimidazole] (OPBI) to fabricate a series of new and highly stable membranes. The membranes were doped with concentrated phosphoric acid at high temperature (120 °C) to form ionically crosslinked structure.…”
mentioning
confidence: 99%
“…25 Liu et al also revealed a new proton transport channel in PA-doped composite membranes composed of poly(arylene ether sulfone) (SPAES) and PBI. 26 Herein, we blended our previously reported sulfonated poly (fluorenyl ether ketone) (SPFEK) with poly [2,2″-(p-oxydiphenylene)−5,5″-benzimidazole] (OPBI) to fabricate a series of new and highly stable membranes. The membranes were doped with concentrated phosphoric acid at high temperature (120 °C) to form ionically crosslinked structure.…”
mentioning
confidence: 99%
“…In past decades, aromatic hydrocarbon polymer electrolyte membranes have been actively investigated as alternatives to the PFSA polymers. These aromatic hydrocarbon polymers, including sulfonated polyimide (SPIs) [3][4][5][6][7], sulfonated poly(arylene ether)s (SPAEs) [8][9][10], and sulfonated polyphenylenes (SPPs) [11,12], have potentials to overcome the issues of PFSA polymers.…”
Section: Introductionmentioning
confidence: 99%